Ultra-compact, broadband Huygens' metasurfaces based on induced magnetism. (17th June 2019) - Xue, Chunhua; Lou, Qun; Li, Teng
Abstract: An ultra-compact, broadband Huygens' metasurface based on induced magnetism has been proposed. The induced magnetism in the Huygens' meta-atom originates from the circulating electric currents constituted by the antisymmetric flowing of surface currents on the both conducting elements. The Huygens' metasurface based on induced magnetism is rather compact and easy to fabricate, and has the abilities of manipulating the transmitted wavefront in a broadband transparency window. As an example of application, the Huygens' meta-lens exhibits excellent antenna performance. The Huygens' metasurface based on induced magnetism offer extra opportunities for broadband wave manipulation in transmissive metasurface.